Pengaruh Kepribadian, Perilaku Kerja dan Inovasi Kerja terhadap Kinerja Pegawai BPS Se-Provinsi Banten - Ning Sri Lestari; Yudha Pratama; Rocky Gumilang; Linaningsih Linaningsih (E-Journal Studia Manajemen, 2022)
This study aims to find the factors that can explain the performance of employees at the Regency / City BPS in Banten Province. The analysis was carried out by examining the influence of personality, work behavior, and work innovation on employee performance. The research approach used a quantitative survey from a total population of two hundred and forty-eight people, one hundred forty-nine samples were selected from the employees of the Regency / City BPS in the Banten Province. An interesting finding from this study is the partial and simultaneous effect of the predictor variables. By paying attention to the R Square value of zero point five hundred and sixty-eight, this means that simultaneously the influence of personality, work behavior, and work innovation on employee performance is fifty-six point eight percent, while the rest is influenced by other factors outside of this research model. . These results conclude that simultaneously and partially, the variables of personality, work behavior, and work innovation can be used as predictor variables for employee performance. The implications and suggestions of these findings are discussed for the benefit of academics and human resource management practitioners